Level of participation of volunteers in volunteering activities in Jerantut District, Pahang - Kamizi, Zayti Nurallya; Yaccob, Yasmin (Human Resource Management Academic Research Society (HRMARS), 2023)
Volunteers are the sole front-liner who are willing to contribute to community services and willing to sacrifice their time and effort without expecting anything in demand. These selfless workers could come from many different backgrounds throughout every corner of our homeland, Malaysia. This study took place in Jerantut district, Pahang with emphasization on characteristics such as gender, type of job, level of education and age. This study aimed to i) describe the demographics of volunteers in Jerantut District, Pahang. (Gender, type of job, level of education, and age); and ii) identify the level of volunteers’ involvement into volunteering activities in Jerantut District, Pahang. This is a quantitative study that utilizes Volunteer Function Inventory (VFI) Questionnaire by Clary et al (1998) as an instrument. The overall analysis of the level of involvement of volunteers in volunteering in activities shows that age has a significant correlation, where the younger the age of the volunteer, the higher the level of involvement with a value of (r= -0.334, p≤0.001). In conclusion, this study shows that younger generation has higher altruistic values that contribute to the involvement in volunteering activities. Therefore, this finding could contribute to aid further organization finding potential volunteers in the future.